1987
DOI: 10.1111/j.1748-1716.1987.tb08282.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteric nerves mediate the fluid secretory response due to Salmonella typhimurium R5 infection in the rat small intestine

Abstract: Eighteen hours after intragastric inoculation Salmonella typhimurium elicited a net fluid secretion in the jejunum and ileum of rats. The mechanisms behind the secretory response were analysed in vivo. Extrinsic denervation of the experimental intestinal segments had no effect. The nerve-blocking agents hexamethonium (i.v.) and lidocaine (serosally applied) blocked the secretion but atropine had no effect. It was demonstrated that the bacteria were invasive by culturing from the intestinal wall. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…These results provide insights into immune mechanisms of tissue dam age, and provide a useful framework for developing strat egies for therapeutic intervention. for EB measurement has previously been described in detail [23][24][25]. In the present study, we further confirmed this from the following observations.…”
Section: Introductionsupporting
confidence: 81%
“…These results provide insights into immune mechanisms of tissue dam age, and provide a useful framework for developing strat egies for therapeutic intervention. for EB measurement has previously been described in detail [23][24][25]. In the present study, we further confirmed this from the following observations.…”
Section: Introductionsupporting
confidence: 81%
“…Because the myenteric plexus is important for functional motility and other gastrointestinal tract functions such as secretion, apoptosis of cells in the enteric nervous system may alter intestinal function. 42 Few apoptotic cells were observed in the serosa, although ischemia and reperfusion and intraluminal distension and decompression cause severe morphologic changes in the equine jejunal serosa. 7 Mesothelial and endothelial cells were apoptotic in the serosa but appeared to be few in number, compared with other layers.…”
Section: Discussionmentioning
confidence: 98%
“…Neurons within the secretomotor reflex pathways are stimulated by bacterial toxins, including cholera toxin (Cassuto et al, 1981;Gwynne et al, 2009) and heat-stable enterotoxin (Eklund et al, 1985;Hubel et al, 1991), and by infective agents, including Salmonella (Brunsson, 1987), cryptosporidium (Argenzio et al, 1996, and rotavirus (Lundgren et al, 2000). The neural circuitry for the pathological activation of secretomotor reflexes is illustrated in Figure 3.…”
Section: Infectious Diarrheamentioning
confidence: 98%